The Viscoelastic Behavior of Legume Protein Emulsion Gels—The Effect of Heating Temperature and Oil Content on Viscoelasticity, the Degree of Networking, and the Microstructure - Lena Johanna Langendörfer; Elizaveta Guseva; Peter Bauermann; Andreas Schubert; Oliver Hensel; Mamadou Diakité (Foods)
Legume proteins are increasingly used in structuring various foods under the influence of heating and stirring energy. Based on available studies, this structuring potential is not yet fully understood. This raises the question of the suitability of legume isolates and concentrates for structuring in emulsion gels and the effect of heat and oil on the gel properties. In this study, soy- and pea-based suspensions and emulsions were prepared with the least gelling concentration using different oil concentrations (0%, 7.5%, 15%, 22.5%, and 30%). The viscoelastic properties were measured before and after heating cycles (65 °C and 95 °C). Scanning electron microscopy images complemented the results. All gels measured showed viscoelastic solid behavior. Thermal treatment showed a positive effect on the gel properties for most samples, especially for concentrates (reduction in the loss factor and networking factor > 1). The concentrates showed much higher networking factors and tighter cross-linking than the isolates. The rheological and microstructural properties of the emulsion gels are influenced by a number of factors, such as carbohydrate content, protein chemistry, the protein purification method, and initial viscosity. Moreover, the influence of oil on the rheological properties depends on the material used and whether oil droplets act as an active or inactive filler.